A Community-Engaged Approach to Creating a Mobile HIV Prevention App for Black Women: Focus Group Study to Determine Preferences via Prototype Demos - Chandler, Rasheeta; Hernandez, Natalie; Guillaume, Dominique; Grandoit, Shanaika; Branch-Ellis, Desiré; Lightfoot, Marguerita (JMIR Publications, 2020)
BackgroundBlack women are an important but relatively overlooked at-risk group in HIV prevention efforts. Although there is an aggregate decline of HIV diagnoses among women in the United States, there are persistent disparate rates of new HIV infections among Black women compared to any other cisgender female subgroup. Strategies to end the HIV epidemic-as outlined in the Ending the HIV Epidemic initiative-for all communities must consider HIV prevention messaging and message delivery mediums that are created with community input. Although mobile health (mHealth) is a popular platform for delivering HIV interventions, there are currently no mobile apps that consider cisgender Black women with the goal of promoting a comprehensive women's reproductive health and HIV prevention lifestyle. Previous research recommends inclusion of the target population from project inception and iteratively throughout development, to promote use of the intervention. ObjectiveThe purpose of this study is to understand cisgender Black women's preferences for functionality, format, and design of a mobile HIV prevention app and to examine their willingness to use an app for HIV prevention. MethodsWe conducted a series of four focus groups with 23 Black cisgender women. Focus groups included discussion and demonstration elements to address cisgender women's general preference for apps, HIV prevention content that would be useful in an app, and preferred app features that would promote use of an HIV-centric app. During focus group discussions, participants were shown narrated, custom wireframes of HIV prevention app prototypes to demonstrate potential app function. ResultsFindings indicated the presence of eight subthemes within the coding structure of three overall themes: (1) health content within the mobile app, (2) mobile app functionality, format, and design, and (3) other suggested features. Specifically, participants detailed preferred educational content, content distribution, app aesthetics, privacy considerations, and marketing of the app. ConclusionsFindings suggest that Black cisgender women preferred an app that integrated HIV prevention and optimal sexual health promotion. Participants provided a range of preferences for content integration and facilitators of app engagement with an HIV prevention app. Preferences centered on gender and cultural congruency of information and content, evidenced by visuals, language, and resources. Black cisgender women are viable consumers for a mobile app-based HIV prevention intervention.